2019
DOI: 10.11646/zootaxa.4554.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Systematic significance of antennal segmentation and sense cones in Thripidae (Thysanoptera: Terebrantia)

Abstract: Variation is discussed concerning the number of antennal segments in adults, and the number of their sense cones, among 182 of the 289 genera of Thripidae. Brief comments are also made concerning antennal structure and sensoria among the other seven terebrantian families. The plesiotypic condition for Thysanoptera is 9-segmented antennae, but fusion between various segments leads to a reduction in number to as few as five segments, and such fusion occurs in unrelated species. In Thripidae, antennal segment III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…1. Antennae segment number: 9-segmented antennae is considered plesiomorphic in Thysanoptera (Mound et al 1980), but in Thripidae the number of antennal segments is unreliable as an indicator of relationships (Zhang et al 2019a). Among the species involved in this analysis, most are 8-segmented, but Smilothrips productus and Ctenothrips dissimilis have 7-segmented antennae, and an occasional specimen of C. distinctus has antennal segments VII-VIII partly fused.…”
Section: Discussion Of Some Character States In These Generamentioning
confidence: 99%
“…1. Antennae segment number: 9-segmented antennae is considered plesiomorphic in Thysanoptera (Mound et al 1980), but in Thripidae the number of antennal segments is unreliable as an indicator of relationships (Zhang et al 2019a). Among the species involved in this analysis, most are 8-segmented, but Smilothrips productus and Ctenothrips dissimilis have 7-segmented antennae, and an occasional specimen of C. distinctus has antennal segments VII-VIII partly fused.…”
Section: Discussion Of Some Character States In These Generamentioning
confidence: 99%
“…The 8-segmented condition of antennae is considered plesiotypic for the family Thripidae (Zhang et al 2019). However, among some Panchaetothripinae genera, including Astrothrips , there are species with the distal segments fused in different combinations, such as segments VI+VII or VII+VIII, or sometimes VI–VIII or even V–VIII forming a terminal group.…”
Section: Taxonomymentioning
confidence: 99%
“…As a result of this fusion the number of apparent segments is reduced to seven, six, or even five. It is important to recognise that reduction in the number of segments is not necessarily a shared apomorphy, because the 7-segmented condition could arise by fusion of either VII+VIII or by VI+VII (Zhang et al 2019).…”
Section: Taxonomymentioning
confidence: 99%
“…The number of antennal segments in adults of the different families and genera in the insect order Thysanoptera varies between five and nine. The plesiotypic number is considered to be nine (Zhang et al 2019), and fossil thrips reported to have 10 to 15 segments (Tong et al 2019) are generally considered to be aberrations in which the terminal segment bears transverse striae. The 9-segmented condition occurs particularly amongst species that exhibit several other characters in a plesiomorphic state, including all Melanthripidae, two genera of Merothripidae, also most species of Fauriellidae, Stenurothripidae, Heterothripidae, and Aeolothripidae (Mound et al 1980).…”
mentioning
confidence: 99%
“…The 9-segmented condition occurs particularly amongst species that exhibit several other characters in a plesiomorphic state, including all Melanthripidae, two genera of Merothripidae, also most species of Fauriellidae, Stenurothripidae, Heterothripidae, and Aeolothripidae (Mound et al 1980). Curiously, members of a few genera of Thripidae (Palmer & Mound 1985;Minaei 2012) also have nine antennal segments, but this is considered a reversion from the 8segmented condition that is assumed to be plesiomorphic for that family (Zhang et al 2019). Variation between eight and nine segments occurs in the genus Anaphothrips, and within that genus a few species exhibit intraspecific variation in antennal segmentation (Mound & Masumoto 2009).…”
mentioning
confidence: 99%